Investigation of Cancer Coping Attitudes of Children Receiving Cancer Treatment between the Ages of 10-18 - Haylı, Çiğdem Müge; Chung, Seockhoon; Canbek, Mediha; Demir Kösem, Dilek; Can, Senanur (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to examine the coping attitudes of children between the ages of 10-18 who are receiving cancer treatment. METHODOLOGY: The data for this research were collected online between September to November 2024. The study group consisted of children between the ages of 10-18 who were receiving cancer treatment. Online questionnaire method, sociodemographic questionnaire form and Pediatric Cancer Coping Scale (PCCS) were used from 85 individuals receiving cancer treatment between the ages of 10-18 who voluntarily participated in the collection of research data and were selected by convenience sampling method, one of the improbable sampling methods, with written consent from their parents. SPSS 25.0 data analysis program was used. RESULTS: Among children between the ages of 10-18 who received cancer treatment, 65.5% were male and 34.4% were female. Examining the coping attitudes of children between the ages of 10-18 who were undergoing cancer treatment, no statistically significant difference was found with the characteristics of gender, age, education level, diagnosis, age at diagnosis, current treatment, duration of treatment, and it was observed that their coping perceptions towards cancer were similar. CONCLUSION: As a result, it is recommended that children between the ages of 10 and 18 who are receiving cancer treatment have personal coping strategies that do not vary according to the characteristics of their cancer and that alternatives for children to cope with cancer should be developed in cooperation with families and nurses.